2015
DOI: 10.16965/ijar.2015.279
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study on Shapes of Pterion

Abstract: Background: Pterion is defined as an H-shaped small circular area formed by the junction of four bones: frontal, parietal, temporal and sphenoid on norma lateralis of the skull, Pterion junction has been used as a common extra-cranial landmark for surgeons in microsurgical and surgical approaches towards important pathologies of this region. Pterion is an important landmark for anterior branch of middle meningeal artery, Broca's motor speech area to the left, insula, the lateral cerebral fissure, for the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Havaldar et al 16 in their study documented 39.20% and 33.60% of sphenoparietal pterion on right and left side, similarly 6% and 10.40% frontotemporal,3.20% and 5.60% were stellate and 1.60% and 0.40% were epipteric type on right and left side respectively similar to the present study, our findings also documented highest number of sphenoparietal type followed by frontotemporal and epipteric. This similarity might be because of similarity in region, similar ethnic group, genetic factor.…”
Section: Discussionsupporting
confidence: 90%
“…Havaldar et al 16 in their study documented 39.20% and 33.60% of sphenoparietal pterion on right and left side, similarly 6% and 10.40% frontotemporal,3.20% and 5.60% were stellate and 1.60% and 0.40% were epipteric type on right and left side respectively similar to the present study, our findings also documented highest number of sphenoparietal type followed by frontotemporal and epipteric. This similarity might be because of similarity in region, similar ethnic group, genetic factor.…”
Section: Discussionsupporting
confidence: 90%
“…However, as imaging techniques continue to develop, it may become possible to use these to determine more precise relationships between bony landmarks and the underlying soft tissues. (10) Sphenoparietal variety was predominant in the human skulls from sources in Gujarat and Awadh area around Lucknow. The present study also showed the same, sphenoparietal variety accounted 81.25% on the right and 86.35% in the left of the skulls of Uttarakhand region.…”
Section: Discussionmentioning
confidence: 98%
“…The distances between the pterion and the lesser wing of the sphenoid and optic canal are of practical importance in surgical approaches to these regions via the pterion. (10) The knowledge on various pterional sutural types and the location of the pterion in relation to bony anatomical land marks are important while performing micro surgeries or mini craniotomy to approach anterior or middle cranial fossa through pterional approach.…”
Section: Discussionmentioning
confidence: 99%
“…Skulls with pathologies such as porotic hyperostosis were also excluded. The morphometric measurements were carried out by measuring the distance from the centre of the pterion to six different locations of the skull including, distance from the center of the pterion to the anterior aspect of the frontozygomatic suture -PSFZ, distance from the center of the pterion to the zygomatic angle -PZAN, distance from the center of the pterion to the zygomatic arch -PZA, distance from the center of the pterion to Henle's spine-PH, distance from the center of the pterion to the mastoid process of the temporal bone -PMP, distance from the center of the pterion to the external occipital protuberance -PI[Figure . 1] [9,10,11,12].…”
Section: Methodsmentioning
confidence: 99%